Type 2 Valvular Heart Disease Affects Decision Making for Anticoagulation in Patients with Atrial Fibrillation: The UMBRIA-Fibrillazione Atriale Prospective Study - Vedovati, Maria Cristina; Reboldi, Gianpaolo; Agnelli, Giancarlo; Verdecchia, Paolo; on Behalf of the Umbria-Fibrillazione Atriale Investigators (TH Open, 2019)
Background Valvular heart disease (VHD) and atrial fibrillation (AF) often coexist.Aim We investigated whether type 2 VHD (other than moderate-severe rheumatic mitral stenosis or mechanical heart valve) influences the prescription of anticoagulants in AF.Methods Umbria-Fibrillazione Atriale is a prospective multicenter registry in patients with AF. For the purpose of this study, type 2 VHD patients were propensity matched with non-VHD counterparts in a 1:1 ratio. Patients with type 1 VHD (moderate-severe mitral stenosis or mechanical heart valve) were excluded.Results We identified 2,212 patients with AF and excluded 46 because data on VHD were unavailable. Type 2 VHD was present in 426 patients (19.7%). Before registry entry visit, 77.1% of type 2 VHD and 66.8% of non-VHD patients were on anticoagulants. At discharge, 90.8 and 85.2% of patients, respectively, were on anticoagulants. After propensity-score matching, 386 patient-pairs were created. In the matched sample, the likelihood of being on anticoagulants before (odds ratio [OR]: 1.43, 95% confidence interval [CI]: 1.02–2.01, p = 0.036) and after (1.63, 95% CI: 1.04–2.57, p = 0.034) the entry visit was higher in type 2 VHD than in non-VHD patients. Patients with type 2 VHD were 70% more likely to receive vitamin K antagonists (VKAs) (OR: 1.70, 95% CI: 1.28–2.27, p < 0.001), and 32% less likely to receive non–vitamin K oral anticoagulants (NOACs; OR: 0.68, 95% CI: 049–0.94, p = 0.011) than non-VHD patients.Conclusion VKAs consistently outperformed NOACs as preferred treatment option in patients with type 2 VHD. This could potentially deny to these patients the well-established benefits of NOACs observed in phase III trials.
Keywords: atrial fibrillation; valvular heart disease; vitamin K antagonists; non–vitamin K oral anticoagulants